Implementing Contextualized Quality Assurance in Islamic Boarding Schools: A Case Study of TMI Al-Amien Prenduan - Ahmadi Ahmadi; Khozin Khozin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Islamic boarding schools (pesantren) face growing demands to implement quality assurance (QA) systems that align with both national education standards and their religious identity. However, few studies offer empirical models for how pesantren can institutionalize QA in context-sensitive ways. This study explores the implementation of QA at TMI Al-Amien Prenduan, a recognized muadalah pesantren in Indonesia. A qualitative case study was conducted using an interpretive paradigm. Data were collected through semi-structured interviews, participant observation, and document analysis. Key informants included pesantren leaders and QA personnel. Data were analyzed using Miles and Huberman’s interactive model, and validity was ensured through triangulation and member checks via focus group discussions. Findings show that TMI implemented a structured QA process using the PPEPP cycle (Determination, Implementation, Evaluation, Control, Improvement). QA practices include internal audits, stakeholder evaluations, and policy documentation. A dedicated QA unit has been established, marking a shift from charismatic, figure-based leadership to an institutionalized system. Key enablers include transformational leadership, capacity building, and external advocacy. Challenges involve limited human resources and cultural resistance to formal systems. The study demonstrates that pesantren can adopt formal QA mechanisms without compromising their identity by contextualizing implementation strategies. The TMI case offers a practical model for similar institutions and supports national efforts to standardize QA in Islamic education.